Drag reduction of stable biomimetic superhydrophobic steel surface by acid etching under an oxygen-sufficient environment - Rong, Wanting; Zhang, Haifeng; Mao, Zhigang; Liu, Xiaowei; Song, Keguan (Materials research express, 2020)
Superhydrophobic surfaces have shown utility applications in drag reduction field. A novel method based on simulation analysis and test experiments is proposed to fabricate a superhydrophobic surface with 3D flower-like micro and nano-structures on a steel ball under an O2 rich environment. The superhydrophobic steel surface has water CA of 166 1.5°. The sliding angle is less than 2°. The experiment and the simulation of the superhydrophobic and the untreated steel ball fall under water are built to prove the validity of the method of reducing water resistance. The drag reduction ratio of the superhydrophobic steel ball is beyond 53% opposed to the untreated surface under water. A model simulation is built to simulate and analyze the solid-liquid interface drag reduction mechanism of superhydrophobic surface based on theoretical analysis. The result testifies the rationality of the drag reduction experiment.